2012
DOI: 10.1080/00207594.2011.626045
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the perception of a familial climate on job performance: Mediation of loyalty to supervisors and moderation of filial behaviour

Abstract: With a collectivist cultural perspective, we examined the positive effects of employees' perceptions of a familial climate on loyalty to supervisors, the mediation of loyalty between perception of a familial climate and job performance, and the moderation of employees' filial behaviour on the relationship between perception of a familial climate and loyalty. The participants consisted of 247 supervisor-and-subordinate dyads in Taiwan. The results supported our hypotheses. Through the mechanisms of family behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Some of the more experienced women were able to leverage this status by assuming the role of an older sister in their relations with clients, which put them in a position of authority even with peers. Previous research supports this postulation: perception of a familial climate enhances loyalty in Taiwanese organizations (Jen, Chou, Lin, & Tsai, 2012). In general, women face greater challenges than men in the workplace as they age (Barnett, 2005;Tang, 2000).…”
Section: Perceived Advantages: Leveraging Gender Roles and Stereotypesmentioning
confidence: 89%
“…Some of the more experienced women were able to leverage this status by assuming the role of an older sister in their relations with clients, which put them in a position of authority even with peers. Previous research supports this postulation: perception of a familial climate enhances loyalty in Taiwanese organizations (Jen, Chou, Lin, & Tsai, 2012). In general, women face greater challenges than men in the workplace as they age (Barnett, 2005;Tang, 2000).…”
Section: Perceived Advantages: Leveraging Gender Roles and Stereotypesmentioning
confidence: 89%
“…491) will promote employee loyalty. Especially within the cultural context of China, a familial climate has been recognized as an influential factor in shaping and explaining employees' behavior, motivation and performance (Jen et al, 2012). Chinese employees who experience a family-like atmosphere at the workplace exhibit a high level of loyalty to their supervisor triggered by social identification (Jen et al, 2012).…”
Section: Leadership Besides Individual Perception and Satisfaction Rmentioning
confidence: 99%
“…Especially within the cultural context of China, a familial climate has been recognized as an influential factor in shaping and explaining employees' behavior, motivation and performance (Jen et al, 2012). Chinese employees who experience a family-like atmosphere at the workplace exhibit a high level of loyalty to their supervisor triggered by social identification (Jen et al, 2012). Similarly, Alvesson (2000) has shown that strong positive corporate social identities as well as strong social relations among peers are important predictors of employee loyalty.…”
Section: Leadership Besides Individual Perception and Satisfaction Rmentioning
confidence: 99%
See 2 more Smart Citations